Microalgae in a global world: New solutions for old problems?. (March 2021) - Vieira de Mendonça, Henrique; Assemany, Paula; Abreu, Mariana; Couto, Eduardo; Maciel, Alyne Martins; Duarte, Renata Lopes; Barbosa dos Santos, Marcela Granato; Reis, Alberto
Abstract: The human population blast has brought several problems related with the overconsumption of a wide range of feedstocks and natural resources conducting to their risk of depletion. The consumption of fossil fuels is an example, with increasing levels of exploitation and negative impacts caused by their use. Anthropogenic activities have triggered the over accumulation of many hazardous substances and wastes which are regarded to be detrimental to life in the Earth and to the various planet ecosystems. There is an urgent need to restore natural resources and unwanted residues and wastes to levels prior the demographic explosion. Microalgal biotechnology appears to be pivotal to achieve this goal in a near future to come. This review presents the current resource problems affecting the Earth and how microalgae are expected to be an important part of the solution, discussing how the production of renewable energy from microalgae can help in an integrated way to mitigate different environmental problems. Microalgae are able to convert wastewaters, CO2 and organic residues in marketable biomass for different uses, including biofuels, converting waste in value. An inventory of current microalgal-based biorefineries in operation as well as a directory of companies, products and applications are also presented. Graphical abstract: Image 1 Highlights: Old pollution problems were highlighted and new solutions are proposed. Microalgae technologies for pollution control have been proposed. Bioenergy production routes were presented. New solutions for bioproducts/biofuels production were presented. Prospects for microalgae biorefineries application were proposed and discussed.